Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis